2010
DOI: 10.1186/1476-4598-9-16
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the transcription factor NF-κB1 by microRNA-9 in human gastric adenocarcinoma

Abstract: BackgroundMicroRNAs (miRNAs) are a new class of naturally occurring, small, non-coding RNAs that regulate protein-coding mRNAs by causing mRNA degradation or repressing translation. The roles of miRNAs in lineage determination and proliferation, as well as the localization of several miRNA genes at sites of translocation breakpoints or deletions, have led to speculation that miRNAs could be important factors in the development or maintenance of the neoplastic state.ResultsWe showed that miR-9 was downregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
123
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 155 publications
(129 citation statements)
references
References 39 publications
4
123
0
2
Order By: Relevance
“…Similar findings indicate that miR-9 plays a tumor-suppressive role via repressing tumor-associated genes (NFκB1 and RAB34) in gastric cancer. 29,33 Significantly, in human cancers, miR-9 expression levels or methylation status are associated with several clinicopathological features, such as tumor grade, metastatic status and survival rate. 23,27,31 Contrary to the above results, it has been showed that miR-9 is significantly deregulated in breast cancer or colorectal cancer, with increasing cancer migration, through repression of α-cadherin or E-cadherin expression.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar findings indicate that miR-9 plays a tumor-suppressive role via repressing tumor-associated genes (NFκB1 and RAB34) in gastric cancer. 29,33 Significantly, in human cancers, miR-9 expression levels or methylation status are associated with several clinicopathological features, such as tumor grade, metastatic status and survival rate. 23,27,31 Contrary to the above results, it has been showed that miR-9 is significantly deregulated in breast cancer or colorectal cancer, with increasing cancer migration, through repression of α-cadherin or E-cadherin expression.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Dysregulation of miR-9 expression has profound effects on physiology and pathology, including cancer, neuronal differentiation and myocardial hypertrophy. [23][24][25][26][27][28][29][30] Several lines of evidence have indicated that miR-9 can function as a tumor suppressor in various cancers. 23,24,27,29,[31][32][33] In gastric cancer, miR-9 is under-expressed and ectopic expression of miR-9 can influence cell growth and the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, miR-375 and miR-142-5p have been identified as classifiers used to recognize recurrence and non-recurrence in gastric cancer; a high frequency recurrence and poor survival were observed in gastric cancer cases with high levels of miR-375 and low levels of miR-142-5p (6). miR-9, which is downregulated in human gastric cancer cells, plays a role in regulating gastric cancer cell growth by targeting NF-jB1 (7).…”
Section: Introductionmentioning
confidence: 99%